The Effect Of Urbanization On Flood Mitigation and Food Security: A Comparative Study Of Rome (Italy) and Semarang (Indonesia) - Mardalena, Ayu (LPPM UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
The rapid acceleration of urbanization, without proper urban spatial policy planning, can have a significant impact on flood mitigation and regional food security, particularly in the urban areas of Rome and Semarang. This study aims to investigate, review, and compare the influence of land use change on food security and flood mitigation in Rome, Italy, and Semarang, Indonesia. The methods used include a literature review and a comparative analysis of scientific publications, reports, and findings from journals published between 2020 and 2023. The findings revealed that urbanization in Rome had a twofold negative effect compared to forest expansion. Moreover, the decrease in natural land in Rome reduced 249,838 tons in productive agricultural areas. On the other hand, urbanization in Semarang resulted in an increase in built-up land area and a decrease in land elevation, leading to a rise in the number of flood events from 23 in 2020 to 63 in 2022. Additionally, urbanization also led to a decrease in agricultural land, reduced water availability for agriculture, and raised the cost of food transportation due to increased distances between production areas and urban centers. Urbanization in both cities poses a threat to the safety of urban residents, particularly through the heightened risk of urban flooding and decreased food security. It is crucial for the government to take charge and establish sustainable regional development by formulating spatial policies for urban areas.